(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
The paper focuses on building envelopes for industrial thermal generating units, their efficiency and its increase. Building envelopes made of lightweight heat-resistant concretes are considered most effective from the point of their building construction, maintenance, repair and cost-effectiveness. One of the unresolved problems here is that porous granular materials suitable for use as concrete fillers operating at temperatures over 1000 OC are not industrially manufactured at the moment The article also characterises commonly used heat resistant porous fillers. It indicates that the use of exhaust zeolites is potentially perspective General properties and characteristics of zeolites are also given. The paper demonstrates that it is quite possible to use exhaust zeolites in building envelopes of lightweight heat-resistant concretes. The work describes testing experiments of typical exhaust zeolites (petrochemical and oil refining industries wastes) in Samara region and the Republic of Tatarstan. Their stress-strain properties and chemical compositions as well as X-ray crystallographic analysis (including analysis under high temperature) are presented. They prove that zeolites are heat-resistant and fire-proof because of corundum formation. Phosphate binder was used for tesing in heat-resistant concretes. The composition of the concrete mixture is given in the paper. As a result, concrete with the following characteristics was obtained: 1550 kg/m3 density, with compressive strength of approximately 21 MPa, having high thermal resistance and maximum permissible application temperature of 1450° c.